Understanding the people confined by the COVID-19 pandemic: a qualitative analysis (Comprendiendo a los confinados por el COVID-19: análisis cualitativo). Issue 3 (2nd September 2021) - Fernandez-Rio, Javier; Ovejero, Anastasio; de la Iglesia, Myriam; González-Calvo, Gustavo; Carriedo, Alejandro; Cecchini, Jose A.; Mendez-Gimenez, Antonio
ABSTRACT: On 15 March 2020, the Spanish population was obliged to confine at home, with no time to prepare. The objective of this study was to analyse the effects this confinement had on the population. 1, 044 citizens (aged 16–84) agreed to participate. The study followed a phenomenological, qualitative research design, and a non-probabilistic snowball sampling was used to recruit the sample. Seven days after the confinement began, a questionnaire including one open question was distributed through social networks, email and the media to an initial wave of participants. They were asked to redistribute it among their contacts to reach a larger and less biased sample. Three positive topics emerged from the data: calm, hope/optimism and spirituality ; and 11 negative topics: concern, weariness, stress/irritability, suspicion, anxiety, sadness, longing, indignation, pessimism, loneliness and depression ; and two that reflected both sides: emotional alternation and resignation . Because significant psychological consequences were observed (post-traumatic stress symptoms, confusion and anger), we believe monitoring the Spanish population's mental health is necessary.